THE INFLUENCE OF CHARACTERISTICS, COMPETENCE AND ENTREPRENEURIAL ORIENTATION ON ENTREPRENEURIAL PERFORMANCE OF NILE TILAPIA FISH BREEDERS IN MINAPOLITAN AREA, NGEMPLAK DISTRICT, SLEMAN REGENCY - Nur Agustini, Rahmania; Irham, Irham; Rahayu Waluyati, Lestari (Universitas Islam Lamongan, 2024)
Ngemplak District is a center for tilapia fish seed production. There are a number of obstacles experienced, namely increasingly tight competition in the seed production business, lack of concentration of human resources in seed production, and seed quality that is not in line with market demand. Based on this problem, the objectives of the study are: to understand the entrepreneurial characteristics of tilapia fish seed producers, to understand the level of entrepreneurial competence possessed by tilapia fish seed producers, to understand the level of entrepreneurial orientation of tilapia fish seed producers, and to understand the influence of characteristics, competence and entrepreneurial orientation on the entrepreneurial performance of tilapia fish seed producers in Ngemplak District. Data processing uses frequency distribution tabulation and arithmetic mean from the Likert scale and regression analysis. The study was conducted on fifty-one seed producers in the Mina Ngremboko Group and Siwar Putih. The results of the study prove: the entrepreneurial characteristics of tilapia fish breeders in Ngemplak District are very high, the entrepreneurial competence of tilapia fish breeders in Ngemplak District is high, the entrepreneurial orientation of tilapia fish breeders in Ngemplak District is high, the characteristics, competence and entrepreneurial orientation significantly influence the entrepreneurship of tilapia fish breeders in Ngemplak District. The results of the study have the potential to improve the economy by maximizing the entrepreneurial performance of tilapia fish breeders in Ngemplak District.